Taxonomic study of the genus Caryanda Stål, 1878 (Orthoptera: Acrididae) from Thailand - Dawwrueng, Pattarawich; Storozhenko, Sergey Yu.; Suwannapoom, Chatmongkon (Zootaxa, 2026)
Until now only two species of the genus Caryanda Stål, 1878 were reported from Thailand. Our study showed more diversity of this genus in the country. Two new species, C. eunigritibia sp. nov. and C. chloronota sp. nov., are described from northern Thailand and C. yunnana Zheng, 1981 is firstly recorded from this country. The species C. neoelegens Otte, 1995 is divided on four subspecies: C. n. neoelegens stat. nov., C. neoelegans zheminzhengi Storozhenko, 2021, stat. nov., C. neoelegans doitungensis ssp. nov., and C. neoelegans nanensis ssp. nov. The hitherto unknown female of C. beybienkoi Storozhenko, 2005 is described. The new Caryanda neoelegens species group is proposed for C. neoelegens and C. beybienkoi. The characteristics of this species group are low sexual dimorphism, coloration of body green or bright green with shining black and white markings on head and pronotum in both sexes, tegmina bicolor, male epiphallus with outer lophi larger than inner lophi, outer lophi always broader than long in anterior view, and apical valves of penis usually short. Keys to Thai species of Caryanda and to subspecies of C. neoelegens are given.